A Decade of LMS Acceptance and Adoption Research in Sub-Sahara African Higher Education: A Systematic Review of Models, Methodologies, Milestones and Main Challenges - Bervell, Brandford; Umar, Irfan Naufal (Eurasia Journal of Mathematics, Science and Technology Education, 2017)
A decade has elapsed since the Learning Management System (LMS) technology permeated its way into higher education in Sub-Saharan Africa (SSA), offering new paradigms of both blended and online mode e-learning delivery. Parallel to other continents, the introduction of LMS stimulated acceptance and adoption intentions among stakeholders in higher education. This necessitated research into faculty members’ and students’ LMS acceptance and adoption intentions. While some research has been conducted in this dimension, the evidential facts are scattered. There is a need to agglomerate these studies to project a better picture of study patterns and results, to be abreast of the current state of the literature and better direct future research. This study sought to bridge the gap by way of a systematic review of previous studies within a decade of LMS acceptance research in SSA, placing them in contextual paradigms of models, methodologies, milestones, subjects, countries, findings and challenges. Results from a systematic review of 31 studies, revealed key determinants of LMS acceptance/adoption to be Attitude and Perceived Usefulness; followed by Performance Expectancy and Perceived Ease of Use; then lastly Social Influence. Major challenges to LMS implementation identified were ICT infrastructure; LMS usage skills and training; LMS system quality, LMS use policy and management support. TAM1 was the dominant model employed and students were the main subject of studies. Moreover, quantitative approach was the preferred design with Regression as the main statistical tool used for data analysis. The study recommended among others that more UTAUT or TAM3 based studies employing mixed method design with instructors as subjects, using structural equation modelling analysis are needed in SSA LMS research. Leadership and top management of higher education institutions should focus more on ICT infrastructure, LMS usage skills/training, LMS quality related issues, support and ICT policy formulation.